Social Entrepreneurship and Sustainable Development: The Case of Social Enterprises in Azerbaijan - Nazila Aliyeva (European Scientific Journal, ESJ, 2021)
The social entrepreneurship theory is still in the conceptualization phase, as each country has individual specifics and approaches to define social entrepreneurship initiatives. The main objective of this paper is to explore the characteristics and backgrounds of social entrepreneurship from Azerbaijan’s perspective, especially its importance in achieving Sustainable Development Goals. To fulfill the objective, there are a few main research questions defined: How do local social entrepreneurs use both business acumen and philanthropic principles to address social, cultural, and environmental challenges? How can Social Entrepreneurship contribute to the Sustainable Development Goals in Azerbaijan?  A qualitative research method was used to gather data through a semi-structured questionnaire. It was found that local social enterprises change the structures and systems that create the conditions for poverty, and the development processes need to consider the link between social entrepreneurship and sustainable development. This paper has significant implications, especially for the stakeholders and policymakers. It indicates the current position of local social ventures about sustainable development and offers some global practices and experiences to improve and facilitate the process and attracts the attention of policymakers on the performance of social enterprises.